(untitled) (Academia Science Repository, 2023)
The teacher is the main person in the educational process of secondary school, if not disabled with this professional is determined, but also to his many xolni this ruxiy and physical health is associated. Thus, the labor of the teacher’s specific special conditions: nerve-emosional downloads, business creativity is a description of the strain of constant attention, the movement of the active low obligatory "which stood" working postures, sound analizator see the outpouring of strain significantly to the hardware shows the effects of very large downloads